We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
635
1
avatar

(3^(4n)-3^(2n))\ (3^(3n) + 3^(2n))

 Jul 29, 2015

Best Answer 

 #1
avatar+22165 
+13

$$\small{\text{$
\begin{array}{rcl}
\dfrac{ 3^{4n}-3^{2n} } { 3^{3n} + 3^{2n} } \\
&=& \dfrac{ 3^{2n+2n}-3^{2n} } { 3^{2n+n} + 3^{2n} } \\\\
&=& \dfrac{ 3^{2n}3^{2n}-3^{2n} } { 3^{2n}3^{n} + 3^{2n} } \\\\
&=& \dfrac{ 3^{2n} (3^{2n}-1) } { 3^{2n} (3^{n} + 1) } \\\\
&=& \dfrac{ 3^{2n}-1 } { 3^{n}+1 } \\\\
&=& \dfrac{ (3^{n}-1)(3^{n}+1) } { 3^{n}+1 } \\\\
\mathbf{ \dfrac{ 3^{4n}-3^{2n} } { 3^{3n} + 3^{2n} } }&\mathbf{=} & \mathbf{3^{n}-1}
\end{array}
$}}$$

 

 Jul 29, 2015
 #1
avatar+22165 
+13
Best Answer

$$\small{\text{$
\begin{array}{rcl}
\dfrac{ 3^{4n}-3^{2n} } { 3^{3n} + 3^{2n} } \\
&=& \dfrac{ 3^{2n+2n}-3^{2n} } { 3^{2n+n} + 3^{2n} } \\\\
&=& \dfrac{ 3^{2n}3^{2n}-3^{2n} } { 3^{2n}3^{n} + 3^{2n} } \\\\
&=& \dfrac{ 3^{2n} (3^{2n}-1) } { 3^{2n} (3^{n} + 1) } \\\\
&=& \dfrac{ 3^{2n}-1 } { 3^{n}+1 } \\\\
&=& \dfrac{ (3^{n}-1)(3^{n}+1) } { 3^{n}+1 } \\\\
\mathbf{ \dfrac{ 3^{4n}-3^{2n} } { 3^{3n} + 3^{2n} } }&\mathbf{=} & \mathbf{3^{n}-1}
\end{array}
$}}$$

 

heureka Jul 29, 2015

4 Online Users

avatar